دراسة بعض الخصائص الحيوية للجراثيم المعزولة من الغشاء الحيوي (Biofilm) في أنظمة شرب مزارع الدواجن - العيسى بشرى (Latakia University Journal -Biological Sciences Series, 2014)
تمّ عزل مجموعة جراثيم من مكونات الغشاء الحيوي (biofilm) وتصنيفها في أنظمة الشرب في عدد من مزارع الدجاج البياض ودجاج اللحم(الفروج) انتمّت إلى , staph. lentus , staph. aureus Pseudomnas aeryginosa ,Citrobacter freundii Pasteurella Multocida ,E. coli Salmonella typhimurium, وحددت جرعة العدوى Infection dose (ID50) وقدر التعداد العام للجراثيم المدروسة في الميليمتر الواحد بوساطة أنابيب العكارة العيارية Macferland Turbidity Standard. كما أظهرت نتائج دراسة فوعة Virulence العزلات المصنفة في أجنة بيض الدجاج المحضن بعمر 11 يوم لدى حقنها وبكمية 0,25 مل في الأغشية السقائية المشيمائية، نفوق أجنة المجموعات المحقونة بالجراثيم بعد 72 ساعة من الحقن بنسبة 80% وبنسبة18% في مراحل متأخرة من التحضين وبنسبة 2% عند الفقس. وفي نتائج دراسة الخصائص الإمراضية Pathogenicity للعزلات المصنفة في أثناء العدوى التجريبية لصيصان فروج لحم بعمر يوم واحد لدى حقنها بالجرعة المعدية عن طريق الفم وعن طريق جوف البطن تراوحت نسبة النفوق الوسطي لصيصان مجموعات التجربة مابين % 40 وحتى %100 ووصفت العلامات السريرية المرضية والآفات التشريحية المميّزة الناجمة عن حقن كلّ نوعٍ من الجراثيم المدروسة. كما تمّ عزل العامل الممرض من كبد ونقي عظام الصيصان النافقة على المستنبتات الجرثومية التمّييزية. Some microorganisms which form biofilms in poultry watering systems in poultry farms (broiler flocks, laying hens) were isolated and classified as follows: staph. lentus, staph. aureus Pseudomnas aeryginosa, Citrobacter freundii, Pasteurella Multocida, E.coli, Salmonella typhimurium. The infectious dose (ID50) was determined depending on the total count of bacteria, and it was performed by the Macferland Turbidity Standard. The results of the virulence study of classified isolates in embryos during the eleventh day of incubation showed that when injected with (0,25ml) in the chorioallantoic membrance, all infected experimental embryos died by 80% after 72 hours, 18% in late stages and 2% during hatching. The results of the study of some pathogenicity characteristics of classified isolates of infected one-day-old chicks showed that the percentage of deaths ranged between 40%-100% during injection with the infectious dose via mouth and via abdomen. The main clinical signs and gross lesion were recorded for each sort of isolated bacteria. The etiologic agent was also isolated from liver and marrow.